تقويم مقرر تعليم المفردات العربية بوصفها لغة ثانية للدراسين الكبار بماليزيا - Osman, Nurulhuda; Sahrir, Muhammad Sabri (Jordanian Academy of Arabic Language, 2020)
Published article in the Journal of Jordanian Academy of Arabic Language, June 2020